Use of Digital Banking in Improving Services at Banks - Marlius, Doni (Universitas Serang Raya, 2022)
This research is useful as a form of digital banking implementation in improving banking services to customers. The sample of this research is the number of digital banking users and the number of customers who have used digital applications from 2021. This study uses qualitative data analysis as a research method that describes descriptively about the application of digital banking in improving banking services and services to customers. analysis in terms of practices that need to be applied, so that it can be seen the extent of its implementation. These results show that the application of digital banking at the Bank is in accordance with the standards set by Bank Indonesia, the application of digital banking can improve the quality of banking services and services as well as increase customer loyalty